2008
DOI: 10.1177/1052562908323191
|View full text |Cite
|
Sign up to set email alerts
|

A Principle-Attribute Matrix for Environmentally Sustainable Management Education and Its Application

Abstract: The environmental threats humanity faces have led businesses to increasingly commit to improve their environmental performance and to increasing attempts to address environmental issues in management education. This article presents a matrix of (a) principles that can underlie and (b) attributes that can be generated by environmentally focused management education and uses the matrix to identify topics, assignments, and assessment mechanisms that can be incorporated into environmental management education. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 46 publications
1
65
0
Order By: Relevance
“…Sustainable development is defined as the "development that meets the needs of the present without compromising the ability of future generations to meet their own need" (Brundtland Commission, 1987, p. 8). Organizational responsibility focuses on the belief that all organizations have a responsibility to strive to become sustainable (Rands, 2009). Finally, personal responsibility addresses the idea that individuals have a responsibility to contribute to sustainable development (Rands, 2009).…”
Section: Ijshe 124mentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable development is defined as the "development that meets the needs of the present without compromising the ability of future generations to meet their own need" (Brundtland Commission, 1987, p. 8). Organizational responsibility focuses on the belief that all organizations have a responsibility to strive to become sustainable (Rands, 2009). Finally, personal responsibility addresses the idea that individuals have a responsibility to contribute to sustainable development (Rands, 2009).…”
Section: Ijshe 124mentioning
confidence: 99%
“…Organizational responsibility focuses on the belief that all organizations have a responsibility to strive to become sustainable (Rands, 2009). Finally, personal responsibility addresses the idea that individuals have a responsibility to contribute to sustainable development (Rands, 2009). For each principle, PAM suggests that successful teaching should impact students' knowledge, skills, and attitudes.…”
Section: Ijshe 124mentioning
confidence: 99%
“…Prior studies emphasized and suggested that environmental education fosters awareness, understanding, and concern that motivate students to take action in their personal and organizational lives to facilitate environmentally sustainable behaviors (e.g., Rands, 2009). The results of the current study indicated that ESCR literacy contents include 43 items in eight categories: knowledge of issues; concept of industrial ecology; ESCR attitude; value; beliefs; locus of control; ESCR sensitivity; and ESCR action strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For the education aspects of a sustainable campus, Rands asserted that campuses should emphasize the awareness of students on sustainability, and further suggested that campuses cultivate their knowledge, attitude and technology on SD [37]. Lüdeke-Freund and Burandt proposed a novel learning system based on three organizational learning models that shift the paradigm from what to learn and to how to learn [38].…”
Section: Introductionmentioning
confidence: 99%